Ebü'l-muîn en-nesefî'de ilâhî ilim - Özgen, Büşra (My University, 2019)
İlâhî ilim meselesi İslâm dünyasında pek çok probleme cevap oluşturacak bir mahiyettedir. İnanç-bilgi ilişkisinden kader mevzusuna kadar ilk dönem tartışmalarında ilim sıfatının farklı yorumlarının etkisinden bahsedilebilir. Bu konunun temel problemleri arasında Allah’ın ilminin zâtı ile ilişkisi, bilgisinin anlamı ve kapsamı, âlim-i mutlak oluşunun insan fiilleri üzerindeki etkisi ve ilâhî ilim ile muhdes ilim arasındaki ilişki gösterilebilir. Bununla birlikte ilmin şümulü diğer sıfatları da bilmeyi gerekli kılmaktadır. Bu sebeple hayat, irade ve kudret sıfatlarının ilim ile alakası anlaşılmalıdır.Zikredilen meseleler, Mâtürîdiyye mezhebinin sistemli bir ekol haline gelmesini sağlayan Ebü’l-Muîn en-Nesefî (ö. 508/ 1115) örnekliğinde incelenmiştir. Nesefî’nin meseleleri çok yönlü bir bakış açısıyla aklı ve nakli referans alarak izah etmesi, ona mezhebi içerisinde farklı bir hüviyet kazandırmıştır. Çalışmamızın hedefi ise ilâhî ilim meselesini ilgili problemlerle Nesefî’nin yaklaşımı temelinde incelemektir. Ancak bilhassa Nesefî’nin görüşlerine atıfta bulunduğu Mu‘tezile, Eş‘ariyye ve Kerrâmiyye mezheplerinin düşüncelerine yeri geldikçe değinilecektir.

The issue of divine knowledge is the solution to many problems in the Islamic world. From the faith-knowledge relationship to the subject of predestination, the effects of different interpretations of the attribute of knowledge can be mentioned in the early discussions. The basic problems of this topic include the relationship between the knowledge of God and His essence, the meaning and scope of His knowledge, the influence of the being of omniscient on human actions and the relationship between the divine and produced knowledge. However, the extension of knowledge requires to know the other attributes. Thus, it must be comprehended the connection of the attributes of life, will and power with knowledge.The matters mentioned were examined in the Abu’l-Muin an-Nasafi (d. 508/ 1115) sample who ensured that the Maturidiyah became a systematic school. Nasafi's explanation of the issues from a multifaceted point of view and reference to reason and transmitted within the context of the logic gave him a different identity within his denomination. The aim of our study is to examine the matter of divine knowledge with related problems on the basis of Nasafi’s approach. Nevertheless, the ideas of Mu’tazilism, Ash’arism and Karamiyyah sects, which were specifically referred to by Nasafi, were discussed as the place came.
Keywords: Abu’l-Muin an-Nasafi; Allah; attribute; bilgi Maturidiyah; Divine Knowledge; Doctrines; Doktrinler; Ebü’l-Muîn en-Nesefî; Faith (Islam); God (Islam); History; Islam; Islam and science; ilâhî ilim; İnanç (İslam); İslam; İslam ve bilim; knowledge; Kuran’ı Kerim; Mâtürîdiyye; Qurʼan; sıfat; Tarih